Transforming Thai University Demonstration Schools into Learning Communities: A User Experience and Design-Based Research Approach - Veepion, Songwut; Sauphayana, Siriphong; Ployduangrat, Jaruwan (Journal of Ecohumanism, 2025)
This study aimed to develop a model for the administration of demonstration schools in public universities based on the concept of "School as a Learning Community" (SLC). The research utilized user experience and design-based research in three phases. Phase 1 involved analyzing the current administrative practices of school administrators under the SLC framework with a sample of 5 administrators. Phase 2 focused on developing a model for promoting SLC-based school administration, targeting 63 participants, including administrators and teachers from Ramkhamhaeng University Demonstration School, Bangna Campus. Phase 3 evaluated the feasibility and suitability of the developed model using a sample of 657 stakeholders, including seven administrators, 52 teachers, and 598 parents of students in grades 1–5. Research tools included interviews and questionnaires, with data analyzed through content analysis, percentages, mean scores (M), and standard deviations (SD). The findings revealed: (1) user experiences highlighted key practices such as inclusive decision-making, shared learning spaces, and stakeholder collaboration, (2) eighteen prototype models for SLC-based administration were developed, integrating stakeholder-driven vision, excellence-focused philosophy, and professional learning community activities, (3) stakeholders most preferred Model 17, selected by 19.33%, emphasizing a shared vision (A2), the philosophy of excellence (B3), and collaborative activity systems (C2), and (4) expert evaluations showed high feasibility (97.40%) and suitability (96.10%) of the proposed model. This study contributes to the literature by providing an actionable framework for transforming demonstration schools into thriving learning communities and fostering collaboration among diverse stakeholders to enhance educational quality and administration efficiency.